2020
DOI: 10.51985/jbumdc2019094
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Syndrome: A Hypochondriacal Distress In Undergraduates– Verity Or Myth

Abstract: Objective: The purpose of this study was to correlate the hypochondriacal concerns related to diseases with level of anxiety and depression symptoms among medical and engineering undergraduates. Study design and Setting: Cross sectional study was conducted among undergraduates of final year students of BUMDC (Bahria University Medical & Dental College) and engineering students from NUST- PNEC (NUST – Pakistan Navy Engineering College). Methodology: In this study; (99) final year medical students and (92) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2 A study conducted in Karachi compared the help-seeking behavior between two groups, medical students and engineering students, and concluded that there is no significant difference between the two groups. 1 This is contrary to the popular belief that medical students tend to avoid seeking medical help when necessary.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…2 A study conducted in Karachi compared the help-seeking behavior between two groups, medical students and engineering students, and concluded that there is no significant difference between the two groups. 1 This is contrary to the popular belief that medical students tend to avoid seeking medical help when necessary.…”
Section: Introductionmentioning
confidence: 92%
“…Medical students' syndrome (MSS) is a combination of psychosomatic symptoms that occur due to students correlating their vague symptoms to medical conditions they recently learned about, 1 whether in their books, lectures, or hospital wards. 2 A study conducted in London has revealed that this phenomenon mainly occurs due to the extensive requirements the average medical student must meet during their preclinical and clinical years.…”
Section: Introductionmentioning
confidence: 99%